Ethnic group differences in obesity in Asian Americans in California, 2013-2014 - Shaoqing Gong; Kesheng Wang; Ying Li; Zhongliang Zhou; Arsham Alamian (BMC, 2021)
Abstract Background Obesity has been generally understudied in Asian Americans. It is important to identify subgroups of Asian Americans at high risk of obesity to help develop targeted interventions for those subgroups. This study aimed to examine the disparities in obesity among Asians (i.e., Chinese, Filipino, Japanese, Korean, and Vietnamese) living in California. Methods A sample of Adult Americans in California (n = 47,970) including Asian American adults (n = 3810) aged 18 years or older were obtained from the 2013-2014 California Health Interview Survey (the U.S. nation's largest state cross-sectional health survey). Body mass index was calculated using self-reported height and weight. Weight status was determined using the WHO Asian BMI cut points in 4 categories: < 18.5 kg/m2 (underweight), 18.5-22.9 kg/m2 (normal weight), 23-27.5 kg/m2 (overweight), and ≥ 27.5 kg/m2 (obese). Multiple logistic regression analyses were used to estimate odds ratio (OR) and 95% confidence interval (CI) after adjustment for covariates. Results Overall, the prevalence of Asians was 23.3% for obesity and 40.0% for overweight. The obesity prevalence was higher in Asians who were males, aged 45-64 years old, had higher family income, were current smokers, never got married, had lower education level, had an insufficient level of physical activity, and had more frequent consumption of fast foods. After adjusting for other factors, compared to Whites, being Hispanics and Blacks were associated with higher odds of obesity (OR = 1.47, 95%CI = 1.31-1.65; OR = 2.04, 95%CI = 1.65-2.53, respectively); being Chinese, Korean, and Vietnamese were associated with lower odds of obesity (OR = 0.28, 95%CI = 0.18-0.45; OR = 0.14, 95%CI = 0.04-0.46; OR = 0.28, 95%CI = 0.14-0.58, respectively). Compared to Chinese, being Japanese and Filipino were associated with higher odds of obesity (OR = 2.75, 95%CI = 1.52-4.95; OR = 2.90, 95%CI = 1.87-4.49, respectively). Conclusions The prevalence of adult obesity was high among Asian Americans in California. Ethnic/racial disparities in obesity among Asian Americans in California were observed in 2013-2014. Compared to Whites, being Chinese, Korean, Vietnamese were associated with lower odds of obesity. Among Asians, compared to Chinese, being Japanese and being Filipino were associated with higher odds of obesity. These findings can help design better interventions to reduce racial and ethnic disparities in obesity, especially for Asian Americans.